2019
DOI: 10.1002/pri.1820
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pulmonary rehabilitation on endothelial function and arterial stiffness in patients with chronic obstructive pulmonary disease

Abstract: Objectives Cardiovascular disease is a major cause of mortality in chronic obstructive pulmonary disease (COPD) and endothelial dysfunction may enhance the mortality risk. Exercise training has shown to be beneficial for improvement of endothelial function in patients with cardiovascular disease, but this remains unclear in COPD. Thus, this study aimed to assess the effect of exercise‐based pulmonary rehabilitation (PR) on endothelium function, arterial stiffness and plasma nitrite levels in patients with COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These studies focused on endothelial function in COPD and showed conflicting findings. [26][27][28] Differences in baseline patient characteristics (age, disease severity) and possibly varying exercise intensities or durations may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…These studies focused on endothelial function in COPD and showed conflicting findings. [26][27][28] Differences in baseline patient characteristics (age, disease severity) and possibly varying exercise intensities or durations may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary rehabilitation has been advocated to improve the functional status of patients with respiratory and cardiovascular diseases [ 11 , 12 ]. Moreover, rehabilitation in patients with chronic pulmonary disease may improve vascular function parameters [ 13 ]. Additionally, scarce evidence in post-COVID-19 patients suggests that endothelium-dependent vasodilation may be ameliorated after cardiopulmonary rehabilitation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary vascular change is an important pathophysiological characteristic of COPD. On the one hand, COPD causes the destruction of the lung parenchyma, which leads to the loss of the attachment of the alveoli and the small airways and the reduction of the elasticity of the lungs [10]. Previous studies [11][12][13] have shown that pulmonary vascular parameters of high-resolution computed tomography (HRCT) of the chest, such as the ratio of the cross-sectional area of small pulmonary vessels to the total area of the lung field (%crosssectional area, CSA), the ratio of pulmonary artery and aorta(PA/A) cross-sectional diameter are potentially related to the pulmonary function indexes.…”
Section: Introductionmentioning
confidence: 99%